Estudo do SnO2 como fotocatalisador para a degradação da rodamina B: fatores limitantes e estratégias para aumento da fotoatividade - Silva, Fernando Barbosa de Freitas (Universidade Federal de São Carlos, 2018)
The photocatalytic activity of SnO2 was assessed according to the surface processing used for its surface activation. Mechanical activation by grinding and hydrothermal treatments under different conditions were applied to the SnO2 particles. It was observed that the grinding of SnO2 particles synthesized by the hydrolysis method resulted in a significant increase in its photocatalytic activity without any phase change. Ball milling was responsible for breaking the xerogel structure and creating defects on the surface of the oxide, which favored hydroxylation/adsorption of water on the surface of the particles, making them more photoactive. Higher hydroxylation/adsorption of water was observed by near infrared spectroscopy (NIR) and also by the generation of hydroxyl radicals using a terephthalic acid solution. The hydrothermal treatment of SnO2 nanoparticles also resulted in a positive effect on photocatalytic activity, but less significant than grinding. The formation of SnO2:Nb2O5 heterostructures from preformed particles was assessed. Milling did not activate the Nb2O5 surface, however, the hydrothermal treatment resulted in surface activation due to the cleaning of impurities. With the best processing conditions of SnO2 and Nb2O5 nanoparticles, the heterostructures were synthesized in a hydrothermal reactor using the preformed nanoparticles. It was observed that heterostructures, in all proportions tested, were more active than the corresponding physical mixtures, the most effective being the one containing 25% of Nb2O5.
Study of SnO2 as a photocatalyst for the degradation of rhodamine b: limiting factors and strategies for photoactivity enhancement
Keywords: Fotocatálise; Óxido de estanho; Óxido de nióbio; Fotoatividade; Degradação fotocatalítica; Ativação mecânica; Heteroestruturas; Nanopartículas; Photocatalysis; Tin oxide; Niobium oxide; Nanoparticles; Photoactivity; Photocatalytic degradation; Mechanical activation; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::FISICO QUIMICA INORGANICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::FISICO-QUIMICA